(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
The notion of the shared origin between calligraphy and painting is an important topic in the history of Chinese art. In this article, we aim to delve into the underlying connection that binds these two domains and to explore their significance in artistic creation. With this purpose, we will analyze the refined aesthetic conceptions presented by Master Shi Tao (1642-1707) in the chapter “Painting and Writing in One” from his seminal work Arts of Painting. This article will unveil that both artistic forms originate from the creative transformation of the “image of the heart,” and that there exists an isomorphic heterogeneity in the relationship between icon, characters, calligraphy, and painting. This pattern of correlation between the arts and nature embodies the ideal aesthetic principle pursued by Chinese artists as they seek a harmonious spiritual concord between humans and the universe.